Evidence for a composite volcano on the rim of Jezero crater on Mars - Sara C. Cuevas-Quiñones; James J. Wray; Frances Rivera-Hernández; Jacob B. Adler (Communications Earth & Environment)
Abstract The Perseverance rover is currently exploring Jezero crater to collect, characterize and cache the first planned samples of Mars for future return to Earth. Orbital and rover observations suggest a volcanic origin for crater floor materials, sources of which have thus far been unknown. Here we describe a mountain on the crater’s southeastern rim with morphological, thermophysical, and mineralogical properties consistent with explosive volcanoes previously identified on Mars and Earth. The mountain’s low thermal inertia and scarcity of superposed impact craters are consistent with a fine-grained, weakly consolidated material such as volcanic ash. Possible flow margins from its northwestern flank extending onto Jezero crater’s floor indicate that it could have plausibly supplied volcanic materials to the crater. If so, then radioisotope dating of igneous rock samples cached by Perseverance could eventually make this the first volcano of precisely known age on another terrestrial planet.